O uso do canabidiol (CBD) no tratamento da epilepsia em crianças: uma revisão da literatura - LOURIDO, Jéssica Sabrina Rebelo (Universidade Federal do Oeste do Pará, 2024)
Epilepsy is defined as a disease that affects children, adults and the elderly in any part of the world, affecting not only the physical as well as the psychological aspects of the patients, therefore it is characterized by two or more unprovoked seizures with an interval of at least 24 hours. Objective: This study aimed to develop a critical analysis of the use of CBD in the treatment of children with epilepsy, listing the main scientific approaches that involve the use of this substance with refractory responses to drug treatment with scientifically proven bases through the literature review. Methodology: The Web of Science Med Line/Pub med database was used as the main source of information. At first, search parameters were used on both platforms, such as: period of publication of research, language and type of study. Results: The anticonvulsant effect of cannabidiol (CBD) in several types of epilepsy has been confirmed by preclinical studies. These studies show a clear therapeutic advantage and good safety in children with therapy-refractory seizures, deserving greater attention and investment in related studies. In addition to the reduction in epileptic seizures, it was also possible to observe, through parents' reports, cognitive and behavioral improvements during treatment. There were cognitive gains in 85.7% of cases with global developmental and behavioral delays, in addition to improvements in 66.7% of cases with behavioral problems. Final Considerations: Despite the controversy and concern on the part of the medical community and parents about the use of CBD, clinical studies confirm the therapeutic effects of CBD, being considered an alternative in cases of refractory epilepsy in children.